The Future of American Undergraduate Education - McPherson, Michael S.; Purcell, Francesca B. (International Higher Education, 2018)
For all of the doubts raised about the benefits of a college education, it delivers on its promises of greater individual and social prosperity. This article provides an overview of work by the American Academy of Arts and Sciences’ Commission on the Future of Undergraduate Education Progress, which offers a national strategy to improve the college student experience. It argues that teaching and learning need to be prioritized so that all students have high-quality postsecondary educational experiences that incorporate a blend of liberal arts and vocational skills. Efforts around improving completion rates and making college more affordable need additional action and there are promising practices to lead the way.